2002
DOI: 10.1177/004051750207200505
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Wax and Its Relationship with Fiber and Yarn Properties

Abstract: In this study, thirty-six cultivars of U.S. upland cotton are selected and their wax content determined by the Conrad method. Both ring spun and open-end yarns are then made from these cottons. Various fiber and yarn properties are measured before and after wax removal using AFIS, HVI, the West Point cohesion tester, and the Uster Tensorapid yam tensile tester, Correlations of wax content with fiber properties and yam properties are analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…The existence of a hydrophobic "cuticle" has only been proven for mature cotton fiber. This strongly OsO 4 -positive, thin (approximately 250 nm wide, approximately 1.3% of fiber weight), morphologically homogeneous outer layer contains an approximately 1:1 mixture of primary wall polysaccharides and wax/cutin molecules, and it is sharply distinct from the underlying cellulosic secondary wall (Yatsu et al, 1983;Cui et al, 2002;Degani et al, 2002;Wakelyn et al, 2007). This structure differs from the bilayered, cuticulated surface of vegetative, epidermal, trichomes, which mixes gradually into an underlying cell wall containing several components (Marks et al, 2008).…”
Section: Relationship Between the Cotton Fiber Tissue And Cuticlementioning
confidence: 99%
“…The existence of a hydrophobic "cuticle" has only been proven for mature cotton fiber. This strongly OsO 4 -positive, thin (approximately 250 nm wide, approximately 1.3% of fiber weight), morphologically homogeneous outer layer contains an approximately 1:1 mixture of primary wall polysaccharides and wax/cutin molecules, and it is sharply distinct from the underlying cellulosic secondary wall (Yatsu et al, 1983;Cui et al, 2002;Degani et al, 2002;Wakelyn et al, 2007). This structure differs from the bilayered, cuticulated surface of vegetative, epidermal, trichomes, which mixes gradually into an underlying cell wall containing several components (Marks et al, 2008).…”
Section: Relationship Between the Cotton Fiber Tissue And Cuticlementioning
confidence: 99%
“…Fiber properties such as length, strength, uniformity and yarn spinning efficiency are no longer entirely satisfactory predictors as our society progresses forward. Instead, surface friction forces that resulted directly from the chemical constituents of fiber cells play an important role in modern costume industry [1]. As derivatives of very long chain fatty acids (VLCFA, fatty acids >C18), waxes are major components of cotton fiber cuticle [2] and display inverse relationships with micronaire, a measure of fiber linear density and fineness [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cotton fiber wax content varies significantly among different varieties. Various studies have reported a strong positive relationship between cotton fibers wax content and their surface area [73,74,[172][173][174]. El Mogahzy showed that the frictional properties of cotton fibers are influenced by their wax content [73].…”
Section: Nanofricitonal and Nanomechanical Properties Of Cotton Fibersmentioning
confidence: 99%